البنوك االلكترونية Banking. E انماطها, التحديات التي تواجهها في اقليم كوردستان العراق - م. هەفال احمد عبدالرحمن عقراوى; م. لقمان قادر عبدالرحمن رواندزى (QALAAI ZANIST JOURNAL, 2021)
Since the uprising spring in 1991 and the formation of the first government in the Kurdistan Region in 1992 heighten attention a lot of information technology and its divisions opened all the existing universities, including public and private universities, this opened the large prospects in use in all areas, and a whole generation of sons appeared region have become experts in the software to work on ready-made applications relying on computers that are designed by private companies, whether they are in Kurdistan or abroad and solving the problem of the quality of the writing (Font) in and databases which use in Kurdish language Sorani dialect, Where previously the problem of Kurdish letters a major obstacle in the use of computers in departments (Official office ) and private companies, and during this period has been a set of software applications designed on PCs for a number of government departments in interfaces multi-lingual, and there are applications only use the Kurdish language. With such a large number of specialist software engineering, banks and have access to advanced degrees and their participation in the sessions and conferences outside the province, but the government did not benefit them in the construction of application software particularly in this area so that it is able to absorb the most important financial business in the region and three interfaces multi-lingual, to see the problems this meet and we do not benefit in a scientific discreet in this area, which will facilitate access to perfection and a goal that please him. In the developed countries and the Gulf in particular countries and the growing ecommerce operations has become a great need for a new type of non-conventional banks in terms using technology beyond the normal pattern of performance does not adhere to a place or a specific time important, and as a result of the accelerating growth of information and communication technology electronic banking, which contributed In came effective in providing a variety of services, low-costs time and place.